Lipoplatin Treatment in Lung and Breast Cancer. (21st December 2010) - Fantini, Manuela; Gianni, Lorenzo; Santelmo, Carlotta; Drudi, Fabrizio; Castellani, Cinzia; Affatato, Alessandra; Nicolini, Mario; Ravaioli, Alberto
Abstract : The introduction of cisplatin in cancer treatment represents an important achievement in the oncologic field. Many types of cancers are now treated with this drug, and in testicular cancer patients major results are reached. Since 1965, other compounds were disovered and among them carboplatin and oxaliplatin are the main Cisplatin analogues showing similar clinical efficacy with a safer toxicity profile. Lipoplatin is a new liposomal cisplatin formulation which seems to have these characteristics. Lipoplatin was shown to be effective in NSCLC both in phase 2 and phase 3 trials, with the same response rate of Cisplatin, a comparable overall survival but less toxicity. A new protocol aiming to elucidate the double capacity of Lipoplatin to act as a chemotherapeutic and angiogenetic agent in triple-negative breast cancer patients is upcoming.